Peningkatan Ketrampilan Menulis Teks Prosedur melalui Penerapan Metode Think-Talk-Write - Tituk Romadlona Fauziyah (Ideguru: Jurnal Karya Ilmiah Guru, 2023)
Students’ writing skill at procedure text is not good enough. The objectives of the research are improving writing skill at procedure text using Think-Talk-Write (TTW) method for students’ class XI science 3 Yogyakarta 10th Senior High School academic year 2021-2022 and describing its implementation in teaching and learning process. It is Classroom Action Research (CAR) with 4 activities are planning, action, observation, and reflection. The research was done in two cycles, and two meetings in every cycle. Students class XI science 3 Yogyakarta are the subject of the research. Collecting data techniques in the research are observation, quiz, practice, and documentation. The result of data analyses was compared to indicators of success and then was concluded. It is showed that by applying TTW method 23 students (64%) gained the minimum mastery criteria in cycle 1 and 33 students (92%) in cycle 2. The increasing is 28%. The indicator of success stated 85% of students gain the minimum mastery criteria, and 92% of students gained it in cycle 2. Thus, the action is successful.